Trends and determinants of neonatal mortality in Uganda: further analysis of the demographic and health surveys - Asiimwe, John Bosco; Nyegenye, Wilson; Muyingo, Edmond (DHS Working Papers No. 151, 2019)
The study examined demographic and socioeconomic factors associated with neonatal deaths in Uganda. Uganda’s neonatal mortality has stagnated at 27 deaths per 1,000 live births over the past decade, risks missing the UN Sustainable Development Goal for reducing neonatal deaths. Studying consistent factors over time that are associated with neonatal mortality could inform policy to reduce it. We used data from the Uganda Demographic and Health Surveys conducted in 2001, 2006, 2011, and 2016. Due to the rare nature of the outcome variable (neonatal deaths), we used a complementary log-log model and controlled for complex survey design in analyses. Our study found that over the past decade children who were not put on breast milk immediately after birth and children of mothers with multiple risk factors for childbearing (too young, too old, too soon, too many) were associated with higher odds of neonatal deaths. We conclude that consistent significant factors associated with increased neonatal mortality include delayed breastfeeding after birth and multiple maternal risk factors. There is a need to sensitize mothers about the importance of breastfeeding newborns immediately after birth. Interventions to reduce the number of teenage pregnancies and promotion of contraceptive use to help avoid higher-risk childbearing are critical to reducing the prevalence of neonatal mortality in Uganda.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The DHS Working Papers series is a prepublication series of papers reporting on research in progress that is based on Demographic and Health Surveys (DHS) data. This study was carried out with support provided by the United States Agency for International Development (USAID) through The DHS Program (#AIDOAA-C-13-00095). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government.